2013
DOI: 10.5588/ijtld.12.0511
|View full text |Cite
|
Sign up to set email alerts
|

Can <I>inh</I>A mutation predict ethionamide resistance? [Short communication]

Abstract: An inhA promoter mutation could be considered as a marker for the determination of ETH resistance in India, where the use of LPA is being expanded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 0 publications
0
26
0
1
Order By: Relevance
“…11 Information provided by molecular DST would better identify patients who would benefit from ETH ( kat G mutations) and those more likely to respond to high doses of INH, avoiding unnecessary exposure to these drugs. 11,17,18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Information provided by molecular DST would better identify patients who would benefit from ETH ( kat G mutations) and those more likely to respond to high doses of INH, avoiding unnecessary exposure to these drugs. 11,17,18 …”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to be aware of the possibility of cross-resistance between low-level INH resistance and ETH, as reported by Schaaf et al in South Africa 33 and Vadwai et al in India. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Ramaswamy and Musser, Basso and Blanchard, identified 6 point mutations in inhA gene (Ile16Thr, Ile21Thr, Ile21Val, Ile47Thr, Val78Ala and Ile95Pro) [15,16]. Recently, in an Indian study, Vadwai et al found 21.4% resistance frequency in inhA gene [17]. The other mechanism for the INH resistance is in the protein encoded by ndh locus.…”
Section: Discussionmentioning
confidence: 99%
“…High-dose INH may be effective [29, 30•] in the case of low drug-resistance levelsas in the case of mutations in the inhA gene and not in the KatG gene (both identifiable by GenoType). Mutations in InhA, in fact, confer low levels of resistance to INH and frequently high levels of resistance to thionamides [31]. Rifapentine cannot be recommended, given its complete cross-resistance with rifampicin.…”
Section: Designing a Regimen For Mdr-tbselection Of Drugsmentioning
confidence: 99%
“…Thionamides should be selected first [24,25] because they are more bactericidal, better tolerated, and less expensive than the other group 4 drugs. However, their efficacy is adversely affected by the presence of an inhA mutation [31], which can be detected by GenoType. The next selection should be cycloserines or terizidone, which are bacteriostatic with limited toxicity and no cross-resistance with other compounds.…”
Section: Groupmentioning
confidence: 99%